2018
DOI: 10.29252/jafm.11.06.28925
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grid Topology on Numerical Simulations of Flow Fields around Wind Turbine Nacelle Anemometer

Abstract: In this paper, the effect of mesh topology on the numerical predictions of the immediate near wake region of a horizontal axis wind turbine is investigated. The present work focuses on the nacelle anemometry measurements. Steady Reynolds Averaged Navier-Stokes (RANS) equations are applied to describe the airflow around the wind turbine nacelle. The k-ε turbulence model is used. To model the turbine rotor, the approach based on the actuator disc concept is considered. The computational domain has been meshed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Based on the last approach, later, Smaı li and Masson (2003), Smaı li and Masson (2004), Masson and Smaı li (2006) works on the nacelle anemometry of typical HAWT rotors have been reported. Mainly, they tackled the impact of rotor aerodynamic key parameters upon the flow features within the nacelle region, especially, around the anemometer location of 600 kW commercially available HAWT at a distance of 5.7 m. Tata et al (2018) also performed a simulation study on nacelle anemometer using ADM approach, with the emphasis on the effect of grid topology upon numerical predictions accuracy. Wind farm large eddy simulations have been conducted by Stevens et al (2018) where comparison using the Actuator Disk Method (ADM) and the Actuator Line Method (ALM) with wind tunnel experiments have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the last approach, later, Smaı li and Masson (2003), Smaı li and Masson (2004), Masson and Smaı li (2006) works on the nacelle anemometry of typical HAWT rotors have been reported. Mainly, they tackled the impact of rotor aerodynamic key parameters upon the flow features within the nacelle region, especially, around the anemometer location of 600 kW commercially available HAWT at a distance of 5.7 m. Tata et al (2018) also performed a simulation study on nacelle anemometer using ADM approach, with the emphasis on the effect of grid topology upon numerical predictions accuracy. Wind farm large eddy simulations have been conducted by Stevens et al (2018) where comparison using the Actuator Disk Method (ADM) and the Actuator Line Method (ALM) with wind tunnel experiments have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…Ameur et al [21] used the 2D and 3D ADM computations in order to study the wind rotor/nacelle interaction in a neutral ABL flow, they found that for complex nacelle geometries the 3D ADM computations are required. Tata et al [22] also performed a simulation study on nacelle anemometer using the ADM approach, with the emphasis on the effect of grid topology upon numerical predictions accuracy. Recently, Amini et al [24] proposed modifications of Snel et al [25] stall delay model empirical coefficients than studied the effect of the proposed modifications on the MEX-ICO rotor using the ADM implemented in OpenFOAM where a certain improvements has been noticed.…”
Section: Introductionmentioning
confidence: 99%